2009
DOI: 10.1007/978-3-642-02728-4_21
|View full text |Cite
|
Sign up to set email alerts
|

Graphics and Semantics: The Relationship between What Is Seen and What Is Meant in Icon Design

Abstract: Visual icons can be considered as a means for designers to convey messages to end-users via the interface of a computer system. This paper explores the relationship between the users' interpretation of icons and the meaning that designers intend icons to convey. Focussing on interface users' understanding of icons, recent research has shown that it is the closeness of the relationship between icon and function, known as the semantic distance, that is of prime importance in determining the success of icon usabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…In total, there were nine 'mediocre' icons (i.e. Icons 3,5,6,7,12,16,17,18,20) which is 42.9% of all icons evaluated in the IRT. All the results for the 'mediocre' icons are listed in Table 12.…”
Section: Test One -'Identifiable' Icon Results (60% -100% Irr)mentioning
confidence: 99%
See 2 more Smart Citations
“…In total, there were nine 'mediocre' icons (i.e. Icons 3,5,6,7,12,16,17,18,20) which is 42.9% of all icons evaluated in the IRT. All the results for the 'mediocre' icons are listed in Table 12.…”
Section: Test One -'Identifiable' Icon Results (60% -100% Irr)mentioning
confidence: 99%
“…In total, there are sixteen 'identifiable' icons (i.e. Icons 1,2,3,6,7,8,10,11,12,13,14,16,17,18,19 and 20) which is 76.2% of all icons evaluated in the IRT. The 'out of context' IRT had already shown that 29.0% of icons were in the this category.…”
Section: Test Two -'Identifiable' Icon Results (60% -100%)mentioning
confidence: 99%
See 1 more Smart Citation
“…size, shape and color) have been allocated to aid the recognition, it is now acknowledged that the correlation between recognition and interpretation also plays a crucial role [39,40]. Interpreting and comprehending a single icon is the simplest process of reading iconographic communication, but when icon interpretation occurs in isolation, it makes icon interpretation too complex [39].…”
Section: Modeling Icon-based Informationmentioning
confidence: 99%
“…The definitions of icon can be divided into two levels of broad and narrow: broad sense-icons are graphical symbols for indication, which have features of highly concentrating, conveying information conveniently and remembering easily [1]. This interpretation contains a wide range, including directory signs in the street, traffic signs, toilet signs, Web graphics, software graphics, and even corporate logo.…”
Section: Introductionmentioning
confidence: 99%